2020
DOI: 10.1021/acs.est.9b05457
|View full text |Cite
|
Sign up to set email alerts
|

Nontarget Discovery of Per- and Polyfluoroalkyl Substances in Atmospheric Particulate Matter and Gaseous Phase Using Cryogenic Air Sampler

Abstract: Novel per-and polyfluoroalkyl substances (PFASs) have become a key issue in global environmental studies. Although several novel PFASs have been discovered in atmospheric particulate matter through nontarget analysis, information on the environmental occurrence of novel PFASs in atmospheric gaseous phases and conventional sampling techniques is somewhat deficient. Therefore, this Article describes a new type of air sampler, the cryogenic air sampler (CAS), which was used to collect all atmospheric components s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 57 publications
(119 reference statements)
2
44
0
Order By: Relevance
“…Here, 38 classes and 117 homologues of PFAS were identified revealing a prevalent occurrence of many PFSAs, some chlorinated perfluoropolyether carboxylic acids and twelve different hydrosubstituted perfluoroalkyl carboxylates (H-PFCAs) in the PM. The authors concluded that novel chlorinated polyether PFAS substances currently used as alternatives to legacy PFAS, require future investigation to elucidate their environmental impact in the ecosystems [98]. As already mentioned, the atmospheric dispersion of PFAS substances has profound consequences in their subsequent transport towards multiple environmental media and receptors since wet/dry deposition mechanisms can account for a significant portion of PFAS entrance into the aquatic and terrestrial ecosystems [42,[99][100][101][102].…”
Section: Pfas Occurrence In the Atmospherementioning
confidence: 96%
“…Here, 38 classes and 117 homologues of PFAS were identified revealing a prevalent occurrence of many PFSAs, some chlorinated perfluoropolyether carboxylic acids and twelve different hydrosubstituted perfluoroalkyl carboxylates (H-PFCAs) in the PM. The authors concluded that novel chlorinated polyether PFAS substances currently used as alternatives to legacy PFAS, require future investigation to elucidate their environmental impact in the ecosystems [98]. As already mentioned, the atmospheric dispersion of PFAS substances has profound consequences in their subsequent transport towards multiple environmental media and receptors since wet/dry deposition mechanisms can account for a significant portion of PFAS entrance into the aquatic and terrestrial ecosystems [42,[99][100][101][102].…”
Section: Pfas Occurrence In the Atmospherementioning
confidence: 96%
“…Perfluoroalkyl and polyfluoroalkyl substances (PFASs) have been extensively used in consumer products and during industrial processes ( Xu et al., 2020a ; Giesy and Kannan, 2002 ). Owing to the high stability of carbon–fluorine (C—F) bonds in PFASs ( Xu et al., 2020b ), these compounds are very stable and frequently detected throughout numerous environmental media, i.e., atmosphere, soil, water, groundwater, and sediments ( Xu et al., 2021 ; Ahmed et al., 2020a ; Yu et al., 2020 ). Unfortunately, with continual usage and long half-lives, PFASs have been detected in aquatic and terrestrial plants and animals, as well as in humans, making them an important focus of study, particularly as a common environmental toxicant worldwide ( Xu et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cl-PFTrEAs was previously only reported in air samples from eastern China. 40 These compounds may represent a new ubiquitous global contaminant class. IDSL.UFA can only confirm isotopic profiles match (Figure S.11); however, a confirmatory fragment ([M-C 3 F 6 O] - ) was observed for the chemistry of C 12 in MS1 which was consistent with the published MS/MS fragmentation (Figure S.12).…”
Section: Resultsmentioning
confidence: 99%